Ankyrin Repeat-Rich Membrane Spanning (ARMS)/Kidins220 Scaffold Protein Regulates Neuroblastoma Cell Proliferation through p21 - Jung, Heekyung; Shin, Joo-Hyun; Park, Young-Seok; Chang, Mi-Sook (Molecules and cells, 2014)
Cell proliferation is tightly controlled by the cell-cycle regulatory proteins, primarily by cyclins and cyclin-dependent kinases (CDKs) in the G1 phase. The ankyrin repeat-rich membrane spanning (ARMS) scaffold protein, also known as kinase D-interacting substrate of 220 kDa (Kidins 220), has been previously identified as a prominent downstream target of neurotrophin and ephrin receptors. Many studies have reported that ARMS/Kidins220 acts as a major signaling platform in organizing the signaling complex to regulate various cellular responses in the nervous and vascular systems. However, the role of ARMS/Kidins220 in cell proliferation and cell-cycle progression has never been investigated. Here we report that knockdown of ARMS/Kidins220 inhibits mouse neuroblastoma cell proliferation by inducing slowdown of cell cycle in the G1 phase. This effect is mediated by the upregulation of a CDK inhibitor p21, which causes the decrease in cyclin D1 and CDK4 protein levels and subsequent reduction of pRb hyperphosphorylation. Our results suggest a new role of ARMS/Kidins220 as a signaling platform to regulate tumor cell proliferation in response to the extracellular stimuli.